Rekomendasi Skema Sistem Satu Data Daerah - Hasudungan, Rocky Gunung; Galistya, Theresia Mutiara; Solana, Aryadi; Aini, Nur; Ngurah Diksa, I Gusti Bagus; Sri Jayanti, Dewa Ayu (Seminar Nasional Official Statistics, 2024)
Indonesia has launched a National Statistics System (SSN) and the One Data Indonesia (SDI) program to ensure standardized and interoperable sectoral statistical data. Jembrana Regency, through the innovation "Jembrana Satu Data Dari Desa (JSDDD)," has demonstrated best practices in regional data management and successfully integrated data down to the village level. This success motivated the author to recommend a Regional One Data System Scheme. This paper emphasizes the importance for regions to have core data as a single source of truth to achieve data interoperability both within local government institutions and with central government. Core data can be obtained through independent village-level data collection, as seen in the JSDDD initiative, or by utilizing census-scale data. The regional office of BPS can play a crucial role as a data steward in auditing and evaluating the quality of regional data. The Regional One Data System can enhance the cost-efficiency of data collection and ensure that data is automatically updated through data registration-based government programs and services.